Climate and the Late Bronze Collapse: New Evidence from the Southern Levant. (20th October 2013) - Langgut, Dafna; Finkelstein, Israel; Litt, Thomas
Abstract : A core drilled from the Sea of Galilee was subjected to high resolution pollen analysis for the Bronze and Iron Ages. The detailed pollen diagram (sample/~40 yrs) was used to reconstruct past climate changes and human impact on the vegetation of the Mediterranean zone of the southern Levant. The chronological framework is based on radiocarbon dating of short-lived terrestrial organic material. The results indicate that the driest event throughout the Bronze and Iron Ages occurred ~1250–1100 BCE—at the end of the Late Bronze Age. This arid phase was identified based on a significant decrease in Mediterranean tree values, denoting a reduction in precipitation and the shrinkage of the Mediterranean forest/maquis. The Late Bronze dry event was followed by dramatic recovery in the Iron I, evident in the increased percentages of both Mediterranean trees and cultivated olive trees. Archaeology indicates that the crisis in the eastern Mediterranean at the end of the Late Bronze Age took place during the same period—from the mid-13th century to ca. 1100 BCE. In the Levant the crisis years are represented by destruction of a large number of urban centres, shrinkage of other major sites, hoarding activities and changes in settlement patterns. Textual evidence from several places in the Ancient Near East attests to drought and famine starting in the mid-13th and continuing until the second half of the 12th century. All this helps to better understand the 'Crisis Years' in the eastern Mediterranean at the end of the Late Bronze Age and the quick settlement recovery in the Iron I, especially in the highlands of the Levant.